Post-heading dry-matter transport and nutrient uptake differentiate hybrid and inbred indica rice in the double-cropping system in South China - Fu, You-qiang; Lu, Chu-sheng; Zhong, Xu-hua; Liang, Kai-ming; Pan, Jun-feng; Liu, Yan-zhuo; Hu, Xiang-yu; Hu, Rui; Li, Mei-Juan; Wang, Xin-yu; Ye, Qun-huan; Yin, Yuan-hong; et al. (Frontiers in Plant Science, 2024)
Introduction: Hybrid rice demonstrated superior performance in enhancing yield and efficiency in rice production compared to inbred rice. Nevertheless, the underlying mechanism responsible for the increased yield and efficiency of hybrid rice in South China's double-cropping rice region remains understudied.Field experiments over two consecutive years were conducted. Firstly, yield variations among 20 inbred and 15 hybrid rice cultivars prevalent in South China's double-cropping rice system were examined. Secondly, selecting representative hybrid and inbred rice cultivars with significant yield disparities were carried out on further analyzing dry-matter production, source-sink relationships, and nutrient absorption and utilization in both rice types.Results: Hybrid rice displayed an average grain yield of 8.07 and 7.22 t hm -2 in the early and late seasons, respectively, which corresponds to a 12.29% and 13.75% increase over inbred rice with statistically significant differences. In comparison to inbred rice, hybrid rice exhibited enhanced nitrogen concentration in leaves at the heading stage (15.48-16.20%), post-heading dry matter accumulation (52.62-73.21%), post-heading dry matter conversion rate (29.23-34.12%), and harvest index (17.31-18.37%). Additionally, grain nitrogen and phosphorus uptake in hybrid rice increased by 11. 88-22.50% and 16.38-19.90%. Hybrid rice mainly improved post-heading nitrogen and phosphorus uptake and transport, while not total nitrogen and phosphorus uptake. Internal nitrogen and phosphorus use efficiency enhanced by 9.83%-14.31% and 10.15%-13.66%, respectively. Post-heading dry matter accumulation, harvest index, grain nitrogen and phosphorus uptake, and internal nitrogen and phosphorus use efficiency exhibited significant positive linear correlations with grain yield.The period from heading to maturity is critical for enhancing hybrid rice yield and efficiency. Improving photosynthetic capacity during this period and promoting nutrient transport to grains serve as crucial pathways for increasing grain yield and efficiency. This study is of great significance for further improvement grain yield and breeding rice cultivars with high-yield and high nutrients use efficiency for South China's double-cropped rice system.